Jews: „Neighbors“ or „Aliens“? Discussion of Ethnic Minorities in Lithuanian Historical Scholarship - Liekis, Šarūnas (Genocidas ir rezistencija, 2002)
This paper is an overview of the Lithuanian historiography on ethnic minorities during the interwar period. It defines two major trends in historical writings of the present day. One is paternalistic and originates from 18th century discussions over the dissidents’ rights, and defines majority-minority relationship as beneficial for the minority’s political and social well-being. It denies conflicts between ethnic groups, and considers the relationship between Lithuanians and Jewish as amicable. In addition, there is a new phenomenon. An interesting fusion of the traditional Zionist discourse of the interwar Jewish-Lithuanian relationship is emerging in Lithuanian historiography. Both views might distort the understanding and perception of the real situation of the Jews in the interwar Lithuania. Therefore, the complex issues of the anti-Semitism, social mobility, and restrictive discriminatory policies of the state have to be addressed. If those issues considered, then the discussion would lead no to the definition of the success of the minority policies, but to the failure in the interwar years. Then introduced should be a definition and analysis of ethnic conflict and this might become all more important in the future discussions of the origin of the relationship between majority and minority in Lithuania.